Improving the quality of tourism human resources in thanh hoa province in the current context (Revista de Investigaciones Universidad del Quindío, 2021)
Thanh Hoa is aiming at developing tourism as a key economic industry in 2030, creating a motivation to impulse socio-economic development, making Thanh Hoa one of the top tourism development provinces of the country. With an aim to attract more domestic and international visitors, apart from improving quality and business environment, diversifying tourism products, Thanh Hoa needs to focus on training and capacity building for tourism human resources of the province. It requires a more professional tourism human resource that is equipped with essential skills to adapt and meet the demand of tourism development at the current period of time. Hence, this article analyses the real situation of tourism human resources in Thanh Hoa Province with a view to presenting relevant forecasts and recommendations on solutions in order to improve the quality of the tourism human resource of Thanh Hoa Province in the current context.
Keywords: tourism human resources; quality of the human resource; tourism development; Thanh Hoa tourism